2012
DOI: 10.1002/hbm.22084
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity for an “Island of sparing” in autism spectrum disorder: An fMRI study of visual search

Abstract: Although autism is usually characterized with respect to sociocommunicative impairments, visual search is known as a domain of relative performance strength in this disorder. The present study used functional MRI during visual search in children with autism spectrum disorder (n = 19; mean age = 13;10) and matched typically developing children (n = 19; mean age = 14;0). We selected regions of interest within two attentional networks known to play a crucial role in visual search processes, such as goal-directed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 64 publications
(94 reference statements)
7
63
2
1
Order By: Relevance
“…In agreement with previous studies that have shown an association between ASD search superiority and ASD symptom severity (Gliga et al, 2015; Joseph et al, 2009; Keehn, Shih, et al, 2013), our correlational analyses demonstrated that faster absent search, reduced leftward bias, and decreased saccade error were associated with increased social and communicative deficits in ASD. This result adds to the small but growing body of evidence that suggests that non-social visual spatial processing strengths are related to sociocommunicative impairments in ASD (see also, Joseph, Tager-Flusberg, & Lord, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous studies that have shown an association between ASD search superiority and ASD symptom severity (Gliga et al, 2015; Joseph et al, 2009; Keehn, Shih, et al, 2013), our correlational analyses demonstrated that faster absent search, reduced leftward bias, and decreased saccade error were associated with increased social and communicative deficits in ASD. This result adds to the small but growing body of evidence that suggests that non-social visual spatial processing strengths are related to sociocommunicative impairments in ASD (see also, Joseph, Tager-Flusberg, & Lord, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Further, we hypothesized that enhanced discrimination (i.e., shorter fixation durations) or peripheral selection (i.e., fewer fixations) would have a disproportionally greater effect for target absent compared to target present trials, as participants are required to complete a more extensive search of the array to confirm that the target is absent. Lastly, given that prior studies have demonstrated that search-related indices are associated with increased ASD symptom severity (Gliga, Bedford, Charman, Johnson, & The BASIS Team, 2015; Joseph et al, 2009; Keehn & Joseph, 2008; Keehn, Shih, Brenner, Townsend, & Müller, 2013), we examined the relationship between response time and eye-tracking measures and ASD symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…This will result in reduced network differentiation, i.e., “muffled” communication between regions within a functional network, and “noisy” crosstalk within non-involved regions. Thus, increased excitation/inhibition ratio might result in altered local functional differentiation (Rubenstein and Merzenich, 2003), which may point out to islets of sparing in ASD, such as the visual cortex, where minicolumns are thought to be more abundant (Keehn et al, 2013). …”
Section: Factors Affecting Connectivitymentioning
confidence: 99%
“…Nevertheless, some reports have also shown abnormal increases in functional connectivity in autism (Muller et al, 2011) or unchanged connectivity (Tyszka et al, 2013). In particular, higher correlation between brain regions has been observed in negatively correlated connections (Anderson et al, 2011d), corticostriatal connections (Di Martino et al, 2011), visual search regions (Keehn et al, 2013), and brain network-level metrics (Anderson et al, 2013a; Lynch et al, 2013). …”
Section: Introductionmentioning
confidence: 99%